A global assessment of Holistic Planned Grazing™ compared with season-long, continuous grazing: meta-analysis findings. Issue 2 (3rd April 2017) - Hawkins, Heidi-Jayne
Abstract : It has been claimed that Holistic Planned Grazing™ (HPG), a type of rotational grazing, can increase productivity in rangelands and reverse climate change while doubling the stocking rate, mainly through the impact of densely bunched animals on primary production. Previous reviews have found similar or greater plant and animal production in continuous (season-long) compared with rotational grazing. Here season-long continuous grazing is compared with HPG alone to explore the evidence for animal impact. Three quantitative meta-analysis models were used to assess data sets from literature between 1972 and 2016. Weighted mean differences (effect sizes) between HPG and continuous grazing showed that there was no difference in plant basal cover, plant biomass and animal gain responses ( p > 0.05). Thus, from the balance of studies, if animal impact is occurring during HPG, it has no effect on production. As interesting as the overall result is the significant between-study heterogeneity assessed using Cochran's Q ( p = 0.007 to <0.0001). Studies with positive effect sizes tended to have higher precipitation ( p < 0.05), suggesting that only some rangelands have the resources to support HPG. Furthermore, there is scope for investigating the impact of HPG on socio-ecological aspects of rangelands, such as management.